Peningkatan Minat Belajar Peserta Didik Melalui Penerapan Model Project Based Learning Pada Pembelajaran Pendidikan Agama Islam Kelas VIII.2 SMP Negeri 2 Suppa Kabupaten Pinrang - Nur Anita; St. Aminah Azis; Buhaerah (Al-Ishlah: Jurnal Pendidikan Islam, 2019)
This study aims to improve student learning in Islamic Religious Education learning through the application of the Project Based Learning (PBL) class VIII.2 model of Junior High School 2 Suppa Pinrang Regency The variable that is the target of this research change is interest in learning. While the action variables used in this study are Project Based learning models. This type of research is classroom action research. The data collection techniques used are observation and documentation. In addition, the data analysis technique using descriptive statistics. The results showed an increase in students’ learning interest from cycle I to cycle II had increased with an average score of 5,52. The improvement starts from the pre-cycle of 2,24 and then the Project Based Learning (PBL) model is implemented through the first cycle, increasing to 3,34 and continued in the second cycle, with a significand increase of 5,52. Thus, a recommendation can be submitted on the aplication of the Project Based Learning (PBL) model to increase students’ learning interest in learning Islamic Education Class VIII.2 junior high school 2 Suppa Pinrang Regency 2018/2019 Academic Year.